Effect of yeast supplementation in diets with early feed restriction on nutrient digestibility and carcass characteristics of broiler chickens - Malahubban, Masnindah; Adek, N. A. N.; Sani, N. A.; Rahimi, N. S. A.; Ab Aziz, Zakry Fitri (IOP Publishing, 2019)
Present study aimed to determine the influence of yeast supplementation in diets with or without early feed restriction on nutrient digestibility and carcass characteristics of broiler chickens. Three dietary treatments each consisting of three replicates namely 1) control (commercial diet); 2) 0.3% yeast supplement; and 3) 0.3% yeast and early feed restriction at 7 to 14 days of age. Faeces were collected from five days before the end of experiment and later analysed for crude protein, fibre, and fat. At the end of the experiment (day-42), two broilers from each replicate were slaughtered. The present study found that crude protein and crude fat increased at 92.00 ± 1.46% and 96.33 ± 0.42%, respectively (P<0.05), over broilers fed commercial pellet only at 84.50 ± 0.56% and 94.17 ± 0.48%, respectively. However, when employing feed restriction on broilers fed on diets with 0.3% yeast, no further improvement (P>0.05) on nutrients digestibility was observed after yeast supplementation in diets. Dressing and abdominal fat of broiler chickens fed a diet with yeast supplement were different (P<0.05) with control. This study concludes that yeast supplementation improved digestibility of crude protein, crude fat, and dressing and abdominal fat but no improvement when early feed restriction imposed.